Nepal orthodox tea: analysis of industry, production, and market potential - Baral, Rudra Bahadur (Kansas State University, 2019)
This study covers industry analysis, financial analysis and market analysis of Nepal orthodox tea. It aims to evaluate the industry forces, analyze the financial performance of firms, and assess market potential. The study is based on field survey, key informants’ interviews, and participant observation in combination with data from secondary sources. The financial information of 65 tea processing firms was collected using standard financial formats. The production and trade related statistical data were obtained from National Tea and Coffee Development Board Nepal, Trade and Export Promotion Center Nepal, FAOSTAT, International Trade Center and STATISTA. The results of industry analysis indicate that in general, tea processors have low bargaining power against input suppliers and tea buyers. The processing industry was found to be less attractive for new entrants. The threat of substitutes was found to be low. But there is intense internal competition among processing firms for resources and markets. Limited and inefficient production, low economies of scale, unorganized supply chain system, limited access to global market are the major binding constraints identified by this study. The results of the financial analysis found positive returns of investment and increasing returns to scale. However, the average capacity utilization of the processing firms is found to be 33 percent. A Cobb-Douglas production function was used to estimate production potential and the result depicted that a one percent increase in the investment in capital, labor and raw material could increase revenue by 0.20 percent, 0.12 percent and 0.68 percent respectively. Thus, this study revealed that the processing firms can decrease processing costs and increase profits by expanding production. The total factor productivity is found to be 3.67 which is the growth of real output not explained by the increase in capital and labor used in the production. The global tea market is growing at the annual compound growth rate of 3.4 percent by volume, 5.7 percent by price and 9.3 percent by value. About 79 percent of the consumers who purchased Nepalese tea rated it excellent. This study informs that there is a promising export potential due to increased demand, competitive price, unique taste and quality products. However, the study shows that about 90 percent of the total exports go to the low-priced Indian market and only 10 percent are exported to premium market. The analysis indicates that China, India, Sri Lanka and Kenya are the major competitor of Nepal. Similarly, Pakistan, Russia, United Arab Emirates and Morocco are potential markets for volume export whereas European countries and North America are potential lucrative markets for specialty Nepalese tea. As a result of foregoing it is recommended that Nepalese exporters diversify and differentiate their market to enhance their profit potential. The findings of this study are particularly relevant to the Nepalese tea processors to improve their competitiveness, production efficiencies, and market share.
Keywords: Tea; Industry analysis; Financial analysis; Market analysis